Design of polar self-assembling lactic acid derivatives possessing submicrometre helical pitch - Bubnov, Alexej; Vacek, Cyril; Czerwiński, Michał; Vojtylová, Terezia; Piecek, Wiktor; Hamplová, Věra (Beilstein journal of nanotechnology, 2018)
Several new lactic acid derivatives containing the keto linkage group far from the chiral part and short alkyl chains have been synthesized and characterised by polarising optical microscopy, differential scanning calorimetry, as well as electro-optic and dielectric spectroscopy. The materials possess a self-assembling behaviour on the nanoscale level as they form polar smectic liquid crystalline mesophases, namely the orthogonal paraelectric SmA* and the tilted ferroelectric SmC* phases, in a broad temperature range down to room temperature. A short helical pitch (≈120-320 nm), relatively high spontaneous polarisation (≈150 nC/cm2) and reasonable tilt angle values have been determined within the temperature range of the tilted ferroelectric SmC* phase. The obtained results make the new materials useful for the advanced mixture design and for further utilisation in electro-optic devices based on the deformed helix ferroelectric effect.
Keywords: keto group; submicrometre helical pitch length; ferroelectric liquid crystal; self-assembly on the nanoscale; soft ferroelectrics